2020
DOI: 10.1038/s41398-020-0699-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence of gender difference in autism spectrum disorder supports the female-protective effect

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder with a male-to-female prevalence of 4:1. However, the genetic mechanisms underlying this gender difference remain unclear. Mutation burden analysis, a TADA model, and co-expression and functional network analyses were performed on de novo mutations (DNMs) and corresponding candidate genes. We found that the prevalence of putative functional DNMs (loss-of-function and predicted deleterious missense mutations) in females was significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 78 publications
4
70
0
1
Order By: Relevance
“…The current male-bias in ASD raises the question of how sex prevalence might be relevant to the underlying mechanisms of this disorder. There are many possible explanations ranging from the differences in the mechanisms involved in males and females to the presence of protective mechanisms in the latter or vulnerability mechanisms in the former (Halladay et al, 2015;Lai et al, 2015;Ferri et al, 2018;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The current male-bias in ASD raises the question of how sex prevalence might be relevant to the underlying mechanisms of this disorder. There are many possible explanations ranging from the differences in the mechanisms involved in males and females to the presence of protective mechanisms in the latter or vulnerability mechanisms in the former (Halladay et al, 2015;Lai et al, 2015;Ferri et al, 2018;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding ASD-related genes, we found Nlgn3 mRNA expression was significantly decreased in DE-SOA-exposed male rats, but not in the female rats in the present study. A recent report has indicated that developmental exposure to PM 2.5 caused autism-like behaviors, such as poor social interaction and repetitive behavior, accompanied by lower oxytocin receptor (OXTR) protein level, catalase activity, and glutathione (GSH) concentration, in 7-week-old male rats [ 59 ]. Different hormonal milieu, receptor type and function, and maturation of neural network may contribute the sex-specific effects in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…However, ascertainment bias for the neurodevelopmental phenotype could also contribute to the male predominance. Nevertheless, it is tempting to speculate that sex-linked traits could affect susceptibility to clinical penetrance and spectrum of SETD1B variants, as female-protective effects have been proposed for other neurodevelopmental disorders 32,33 .…”
Section: Discussionmentioning
confidence: 99%